Varietal characterization of okra (Abelmoschus esculentus) based on morphological descriptions - SINGH, B; CHAUBEY, T; UPADHYAY, D K; JHA, AASTIK; PANDEY, S D; SANWAL, S K (The Indian Journal of Agricultural Sciences, 2015)
A total of 36 cultivars of okra [Abelmoschus esculentus (L.) Moench] were grouped for 31 morphological characters (17 visual and 14 quantitative) adopted as per DUS guidelines. All the cultivars showed similar expression for each characters over the four consecutive year (kharif, 2010, 2011, 2012 and 2013) depicting the stability of cultivars. None of the attributes showed intra-varietal variations. Three cultivars, i.e. Azad Bhindi 3, Kashi Lalima and VROR 159 showed red stem colour while others have green stem colour. No. 315 showed first flower at less than 5 nodes while SB 2, Arka Abhay, Kashi Vibhuti, Kashi Pragati, Kashi Lila and Perkins Long Green exhibited first flower at 5-8 nodes, whereas other cultivars expressed first flower appeared at more than 8 nodes. Cultivars Pusa A-4, Kashi Leela and Punjab Padmini were early in flowering (<35 days) while SB 2, Arka Anamika, Punjab 8, Kashi Pragati, HRB 55, Varsha Uphar, Hisar Naveen and Arka Abhay were medium (35-45 days), whereas other cultivars were late (>45 days) in flowering. Purple leaf vein colour was observed in 7 cultivars, viz. Susthira, Arka Anamika, Azad Bhindi 3, Kashi Lalima, Punjab Padmini, No. 315 and Perkins Long Green and the other cultivars depicted green leaf vein colour. Inside purple base colour of petal was exhibited in eight cultivars, viz. SB 2, No. 136, Susthira, Arka Anamika, Azad Bhindi 2, HRB 55, Azad Bhindi 1 and Punjab 7 while the other cultivars showed both side purple base colour on both side of petal. Light green fruit colour was observed in 8 cultivars, viz. GO 2, GJO 3, Azad Bhindi 2, Dl-87-5, Arka Abhay, VRO-3, Pusa Sawani and BO 2, whereas Azad Bhindi 3 and Kashi Lalima had light red fruit colour and rest of cultivars showed green fruit colour. Length of fruit (cm) at marketable stage (four days after anthesis) varied from small to long in the cultivars studied. Only one cultivar SB-2 have small fruit length while Susthira, Varsha Uphar, Kashi Vibhuti, Dl-87-5 and No.136 showed long fruit length. Rest cultivars showed medium fruit length. Only three cultivars, viz. Susthira, No. 315, and Kashi Vibhuti exhibited short plant height (<90cm). Majority of the cultivars were classified under medium (90-120cm) and tall (>120cm) plant height group.